1989
DOI: 10.1042/bj2640397
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of uroporphyrinogen III synthase (co-synthase) from an overproducing recombinant strain of Escherichia coli K-12

Abstract: The Escherichia coli hemD gene, encoding the enzyme uroporphyrinogen III synthase (co-synthase), was cloned into multi-copy plasmids in E. coli cells that were used to generate strains producing up to 1000 times the concentration of the synthase in the wild-type. The enzyme was purified to homogeneity from these strains in milligram amounts. The enzyme is a monomer of Mr 28,000 with an isoelectric point of 5.2 and a pH optimum of 7.8. The specific activity of the purified synthase is 1500 units/mg and the Km f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 23 publications
0
16
2
Order By: Relevance
“…The present study indicates that PfPBGD also has UROS activity leading to the formation of UROGEN III. While information on an independent UROS gene and purification of the enzyme is available from different sources such as E. coli (33), yeast (34), and the human (35) including its crystal structure (36), there have been no reports on the enzyme or gene from algal and plant sources (37). Interestingly, it has been reported that in Leptospira interrogans hemC codes for a bifunctional PBGD/UROS enzyme (38).…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicates that PfPBGD also has UROS activity leading to the formation of UROGEN III. While information on an independent UROS gene and purification of the enzyme is available from different sources such as E. coli (33), yeast (34), and the human (35) including its crystal structure (36), there have been no reports on the enzyme or gene from algal and plant sources (37). Interestingly, it has been reported that in Leptospira interrogans hemC codes for a bifunctional PBGD/UROS enzyme (38).…”
Section: Discussionmentioning
confidence: 99%
“…The advent of recombinant-DNA technology allowed the enzyme to be produced in much larger quantities (139,140), and the development of a fluorescencebased assay (141) coupled with more accurate high-performance liquid chromatography (HPLC) analysis to separate the type I and III isomers made the assays much more rapid and accurate (142). Consequently, after the initial laborious methods to isolate the first purified UroS enzyme from human blood (143), quite a few UroSs from a variety of organisms were subsequently purified as a consequence of recombinant-DNA approaches (144)(145)(146)(147). UroSs are generally monomeric species with molecular masses of around 30 kDa.…”
Section: Dailey Et Almentioning
confidence: 99%
“…3 ( Fig. 2A) which is higher than that observed for the E. coli (pH 7.8) [8] and human (pH 7.4) [6] enzymes although similar to that obtained for the enzyme isolated from Euglena (pH 8.25) [5]. Due to the increased stability of uro'gen I11 synthase from B. subtilis, it was possible to investigate the optimum temperature for enzymic activity (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…1B) established a subunit mass for the enzyme of 32 5 0.5 kDa. Uro'gen I11 synthase from B. subtilis is therefore clearly a monomeric enzyme, in common with those isolated from other sources [5,6,8,201. The predicted subunit mass for uro'gen I11 synthase from B. subtilis, calculated from the aminoacid composition derived from the DNA sequence of the hemD gene, is 29.1 kDa [lo].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation